The Policy Enabling Environment for Climate Smart Agriculture: A Case Study of California - Lewis, Josette; Rudnick, Jessica (Frontiers in Sustainable Food Systems, 2019)
Climate smart agriculture (CSA) provides a framework for balancing multiple dimensions of agriculture and food systems in an era of climate change: addressing agricultural contributions to global greenhouse gas emissions, vulnerabilities to climate change impacts, and the relationship between agricultural productivity, incomes and food security. As the global climate agenda more thoroughly integrates the CSA framework, policy makers often search for “triple wins”—practices that can mitigate emissions, increase resilience or adaptation, and increase productivity. Agriculture and food systems however, are complex systems with many agroecological and sociopolitical interdependencies. In many cases, there are necessary tradeoffs among the three CSA objectives, as advancement in one area may negatively impact another. A major challenge to implementing CSA across multiple geographies thus lies in the coordination of policies and programs that recognize these tradeoffs and allow for prioritization or reconciliation among the three objectives when there are conflicts. This paper describes California's adoption of CSA principles to illustrate how synergies and trade-offs are addressed in a policy framework that spans regulatory measures, incentive programs, research, and technological development, that is both climate specific and arising from other simultaneous environmental and economic priorities. We provide specific examples where agriculture has benefited and where it is constrained due to the balancing of CSA objectives, and discuss how the policy environment has evolved over time in attempts to deal with the complexity of the agriculture-climate nexus. This case serves to summarize and analyze the implemented CSA initiatives in one of most productive and well-resourced agricultural regions of the world; however, lessons learned from California can serve as transferable knowledge for other regions around the globe who are currently developing CSA policies and plans. Our findings suggest that cross-sectoral collaboration, policy coordination, and inclusion of a diverse set of stakeholders are fundamental to the efficacy of CSA strategies in complex and ever-evolving environmental and sociopolitical conditions.